Mapping Constitutional Law Studies Through Bibliometrics (2005–2024): Challenges and Opportunities - Rusmini, Rusmini; Evi Oktarina (Nurani, 2024)
This study seeks to explore and analyze constitutional law research published in the Scopus database over the past two decades, from 2005 to 2024. Using bibliometric analysis combined with VOSviewer software, it examines trends, patterns, and developments in the field during this time frame. The findings reveal that constitutional law studies published over the last two decades have yet to provide a comprehensive contribution. Based on these findings, the study highlights the need for constitutional law research that focuses on the adaptation and transformation of legal orientations in the era of globalization, both conceptually and in practical application. By addressing these processes, future challenges in constitutional law can be more effectively managed, paving the way for a more progressive legal system. The study underscores the importance of bold and forward-thinking constitutional law research that tackles fundamental issues and offers transformative solutions for the governance of national legal systems.